Efektivitas Penggunaan Quick Response Code Indonesian Standard (QRIS) Sebagai Alat Pembayaran Di Kalangan Generasi Baru Indonesia Purwokerto Berdasarkan Akad Wadi’ah - Danica Salsava Tanusi; Saepudin, Encep (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
The purpose of this study was to determine the effectiveness of using the QRIS feature as a means of payment among GenBI Purwokerto, to determine the factors that influence interest in using QRIS as a means of payment among GenBI Purwokerto, and to determine the implementation of the wadi'ah contract on the use of QRIS as a means of payment. The method used was qualitative method with the type of field approach (field research). The data collection techniques used were observation, interview, documentation. The results of this study indicate that QRIS as a means of payment among GenBI Purwokerto is effective that using QRIS is universal, easy, profitable, direct, the factors that influence GenBI Purwokerto using QRIS provide speed, convenience, cheap, safe, and reliable in the transaction process and the implementation of the wadi'ah contract, especially the wadiah yad adh-dhamanah contract occurs between the issuer and the e-money holder, where when carrying out the transaction process the nominal amount paid automatically goes to the e-money holder's account by being entrusted to the issuer.